Friction power loss in ball bearings: Correlation with bearing skidding and cage motion stability - Mingkai Wang; Linbo Zhu; Kim Tiow Ooi; Haizhen Li; Ke Yan; Jun Hong (Friction)
This study introduces a prediction method for bearing friction power loss, focusing on the interplay of bearing skidding and cage motion stability on the tribological properties of ball bearings. The internal friction source is first identified in eight forms according to the interaction analysis among bearing components. Then, the ring flexibility generated by the assembly state of a rotor-bearing system and the cage flexibility caused by the centrifugal effect are considered, and the effects of the spatial displacement of outer ring and contact force on the outer ring deformation are also analyzed. Furthermore, the traction effect of the ball-raceway and the hydrodynamic lubrication of the cage-guiding ring are discussed to establish an improved bearing dynamic model. The validity and reliability of the present method are confirmed through a comparative analysis with experimental data. Finally, the relationships between the dynamic behavior and friction power loss are investigated. The results highlight the critical role of the friction loss of bearing components subjected to lubricant viscosity resistance and the sliding friction loss of the cage-guiding ring in determining the total tribological properties. The dynamic behavior can also be optimized by adjusting the bearing preload and cage structure to effectively weaken the bearing friction power loss.